Efeitos indiretos das aranhas Peucetia spp. (Oxyopidae) e Misumenops argenteus (Thomisidae) no sucesso reprodutivo de Trichogoniopsis adenantha (DC) (Asteraceae) e no comportamento das guildas associadas à planta - Grisolia, Bruno Barufatti [UNESP] (2014)
Although predators may exert different effects on the behavior of pollinators, parasitoids and phytophagous, little is known about its effects on the risk behavior of these three guilds in the same system. We performed a experimental study to investigate the contrast in foraging behavior between phytophagous, pollinators and parasitoids, manipulating an atmosphere of predation risk on reproductive branches of Trichogoniops adenantha (DC) in the Serra do Japi, Jundiaí, SP. For this, we compared the number of visits to flowers with and without predators. Additionally, we used two species of spiders, Peucetia rubrolineata (Oxyopidae) and Misumenops argenteus (Thomisidae), which use different hunting strategies and forage in different parts of plant. Phytophagous decrease over 50 % of visits when exposed to predator, and avoided carrying flowers indistinctly with P. rubrolineata or M. argenteus. Among the pollinators, predators recognition is taxa specific. In this case, only the bees avoided flowers with M. argenteus, which decreased 60% in the number of its visits. We purpose that the contrast among guilds occur due to the existence of different taxonomic groups. These data provide a new perspective for studies of predation risk, demonstrating that the effect of predators can be distinguished according to the guild observed in the system. How different guilds may cause distinct effects for plant reproductive success, it is important to contemplate the contrast effects of risk behavior among guilds in studies that focus on trophic cascades. The constrating results observed for the different guilds, in particular, the fact of the phytophagous avoiding plants with spiders can be indirectly positive for the reproductive success of plant (i.e. the presence of spiders could influence biotic protection of the plant). Most studies on biotic protection of a plant uses only one kind of predator . However, a current challenge for ecology is to...